Poly(propylene fumarate)-based materials: Synthesis, functionalization, properties, device fabrication and biomedical applications. (July 2019) - Cai, Zhongyu; Wan, Yong; Becker, Matthew L.; Long, Yun-Ze; Dean, David
Abstract: Poly(propylene fumarate) (PPF) is a biodegradable polymer that has been investigated extensively over the last three decades. It has led many scientists to synthesize and fabricate a variety of PPF-based materials for biomedical applications due to its controllable mechanical properties, tunable degradation and biocompatibility. This review provides a comprehensive overview of the progress made in improving PPF synthesis, resin formulation, crosslinking, device fabrication and post polymerization modification. Further, we highlight the influence of these parameters on biodegradation, biocompatibility, and their use in a number of regenerative medicine applications, especially bone tissue engineering. In particular, the use of 3D printing techniques for the fabrication of PPF-based scaffolds is extensively reviewed. The recent invention of a ring-opening polymerization method affords precise control of PPF molecular mass, molecular mass distribution ( Ɖ M ) and viscosity. Low Ɖ M facilitates time-certain resorption of 3D printed structures. Novel post-polymerization and post-printing functionalization methods have accelerated the expansion of biomedical applications that utilize PPF-based materials. Finally, we shed light on evolving uses of PPF-based materials for orthopedics/bone tissue engineering and other biomedical applications, including its use as a hydrogel for bioprinting. Graphical abstract: Image 1